1968
DOI: 10.2323/jgam.14.217
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Water in Spores of Bacillus Megaterium

Abstract: Several physical properties of spores of Bacillus megaterium, such as vapor pressure isotherm, complex dielectric constant, nuclear magnetic resonance absorption spectrum, as well as water sorption and desorption rates, were studied in comparison with those of vegetative cells of the same organism with respect to content and form of the cell water. Spores showed larger water content as compared with vegetative cells in the humidity range of less than 78% (R. H.) at 30°, while they showed smaller water content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Determination and quantification of water content in spores has been extensively carried out by NMR. Vegetative cells showed narrower absorption peaks in NMR spectra than spores, indicating that water molecules in spores lack mobility in their rotational and\or exchange motions (Maeda et al, 1968). In the same study, no differences in the time course of water absorption and desorption were found between spores and vegetative cells, which suggested that immobilized water molecules could be driven off IP: 52.183.12.225…”
Section: Introductionsupporting
confidence: 49%
“…Determination and quantification of water content in spores has been extensively carried out by NMR. Vegetative cells showed narrower absorption peaks in NMR spectra than spores, indicating that water molecules in spores lack mobility in their rotational and\or exchange motions (Maeda et al, 1968). In the same study, no differences in the time course of water absorption and desorption were found between spores and vegetative cells, which suggested that immobilized water molecules could be driven off IP: 52.183.12.225…”
Section: Introductionsupporting
confidence: 49%
“…4(a) and (a). The curves are typically a, value sigmoid and similar to those for proteins (Bull, 1944) and to those previously obtained for spores (Waldham & Halvomn, 1954;Neihof et al, 1967;Maeda et al, 1968).…”
Section: (F) Watersupporting
confidence: 84%
“…Dielectric permittivity data (11) and electron paramagnetic resonance spectra (12) suggest that most ions in the core are immobilized, 13 C NMR spectroscopy indicates that the core's large depot of pyridine-2,6-dicarboxylic acid (dipicolinic acid, DPA) is in a solid-like state (13), and fluorescence measurements show that green fluorescent protein is at least 4 orders of magnitude less mobile in the dormant core than in the cytoplasm of the vegetative B. subtilis cell (14). Although these observations are consistent with a glassy core, attempts using 1 H NMR linewidths to directly measure water mobility in spores have not been conclusive (15,16), partly because of the confounding effect of paramagnetic Mn(II) ions.…”
mentioning
confidence: 68%